A plant-ant interaction in the Brazilian Savanna: The interesting case of Alibertia edulis (Rich.) A.Rich (Rubiaceae) and Camponotus rufipes (Fabr.) (Formicinae) - Pilon, Natashi A.L.; Rasteiro, Luana Grenge [UNESP]; Carneiro, Tainah Eduarda Boian [UNESP]; Martins, Aline Redondo [UNESP] (Elsevier, 2024)
Plant-ant interaction in savanna ecosystems is an iconic example of species mutualism. In Cerrado, Brazilian savanna, it is common to find this type of interaction mediated by the offer of extrafloral rewards. This study described a new plant-ant interaction for the tree Alibertia edulis (Rubiaceae) and the ant species Camponotus rufipes and elucidated the main structure involved in the interaction. To do so, (i) we monitored the phenology of A. edulis, (ii) recorded the ant species visitation, and, (iii) collected fruits in different stages of development to perform anatomical and histochemical trials to characterize the structures and chemical components related to the secreted substances - which could be responsible for attracting the ants. Ants’ visitation starts at the beginning of fruit development and stops when they are completely ripe. An extrafloral nectary – pericarpical nectary - on the top of the fruits was identified and described for the first time in the Alibertia edulis, derived from the flower structure, which remains to exude (sugar components) during the fruit development. Based on these results, C. rufipes, known for being an aggressive ant, may play a role in protecting fruits against predation until they are completely ripe and the seeds are ready to be dispersed. During seed dispersal, the fruits reduce the production of nectar, signaling the end of the partnership with the ants until the next reproductive season. Here, we shed light and bring new insights into a new plant-ant interaction for a widely spread tree and ant species.
Keywords: Anatomy; Mutualism; Pericarpial nectary; Phenology; Plant-ant interaction; Savanna